LAND ZONING FEATURES IN SETTLEMENT - Isachenko, N. V. (Землеустрій, кадастр і моніторинг земель, 2011)
The principle of zoning of lands is defined by the Land Code of Ukraine where it is specified thst zoning of lands is carried out within settlements and requirements of rather admissible types of building and other use the land lost within separate zone according to local rules of building are established. However many aspects of studied questions are studied insufficiently both with methodical, and from the practical point of view, in particular,approaches, principles, classificstion signs and feature of land zoning, and also mechanisms of introduction of thas system.